NKG2A and circulating extracellular vesicles are key regulators of natural killer cell activity in prostate cancer after prostatectomy - Yu‐Chuan Lu; Chen‐Hsun Ho; Jian‐Hua Hong; Ming‐Chieh Kuo; Yi‐An Liao; Fu‐Shan Jaw; Jason Chia‐Hsien Cheng; Chao‐Yuan Huang; Ko‐Ping Chang; Chung‐Hsin Chen; Jung‐An Lin; An Hsiao; et al. (Molecular Oncology, 2023)
Extracellular vesicles (EVs) are an important regulatory factor for natural killer cell activity (NKA) in the tumor microenvironment. The relationship between circulating EVs in the peripheral blood and natural killer (NK) cells in prostate cancer (PCa) is unclear. This study aimed at investigating the key regulators in the interaction between circulating EVs and NK cells in PCa patients before and after tumor removal. NK‐cell characteristics were prospectively assessed in 79 patients treated with robot‐assisted laparoscopic radical prostatectomy preoperatively and postoperatively. Compared with healthy donors, the existence of prostate tumors increased the number of circulating EVs and altered ligand expression of EVs. Circulating EVs extracted from cancer patients significantly decreased NKA of NK cells compared with those extracted from healthy donors. Upon treatment with an inhibiting antibody or small interfering RNA, natural killer cell protein group 2A (NKG2A) was identified as the main NKA regulator in cancer patients for accepting the signal from circulating EVs. After surgery, NKA was increased and NKG2A expression on NK cells was significantly reduced. The expression of ligands for natural killer cell protein group 2D (NKG2D) on EVs and the level of circulation EVs both significantly increased. With the decrease in NKG2A levels on NK cells and the increase in total NKG2D ligands on circulating EVs, which was increased postoperatively, both NKG2A on NK cells and NKG2D ligands on circulating exosomes are main regulators of NKA restoration after prostatectomy.